Contextual Factors Shaping First-Year Students’ Academic Adjustment: Evidence from Education Institutions in Battambang, Cambodia - Bunrosy Lan; Rany Sam; Vireak Keo; Wen Rouet (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: This study investigates the multifaceted factors influencing first-year students' academic adjustment in higher education institutions in Battambang, Cambodia. Specifically, it examines the factors integrating perspectives from educational psychology and sociocultural theory. Methodology: A quantitative research design was employed using a structured questionnaire administered to 350 freshmen from two institutions during the 2023–2024 academic year. Data were analyzed using SPSS version 25 through descriptive statistics, exploratory factor analysis, hypothesis testing, independent sample t-tests, and ANOVA. Main findings: The results show that ICF, SCF, MEF, and AAF significantly predict academic adjustment, explaining for 47.9% of the variance (R² = 0.479, p < .000), while INF showed no significant effect. The findings highlight the importance of both institutional and socio-emotional dimensions in shaping students’ adaptation to academic life. Novelty/Originality of this study: This study adopts an interdisciplinary approach, drawing on educational, psychological, and sociocultural frameworks to provide a more holistic understanding of student adjustment. Its findings can inform socially institutional practices that enhance first-year student support, teaching quality, and cultural responsiveness. Encouraging active student engagement and peer support mechanisms can further contribute to improved academic transition and retention in the Cambodian higher education context